EFL College Student’s Perception in Using Movie Animations from Little Fox Youtube Channel as Autonomous Learning Activities - Zahra, Nadafa Namira; Marlina, Leni (Universitas Negeri Padang, 2024)
The aim of this research is to reveal students' perceptions of the use of movie animations from the